t-PA Suppresses the Immune Response and Aggravates Neurological Deficit in a Murine Model of Ischemic Stroke - Draxler, Dominik F.; Lee, Felix; Ho, Heidi; Keragala, Charithani B.; Medcalf, Robert L.; Niego, Be'eri (Frontiers in Immunology, 2019)
Introduction: Acute ischemic stroke (AIS) is a potent trigger of immunosuppression, resulting in increased infection risk. While thrombolytic therapy with tissue-type plasminogen activator (t-PA) is still the only pharmacological treatment for AIS, plasmin, the effector protease, has been reported to suppress dendritic cells (DCs), known for their potent antigen-presenting capacity. Accordingly, in the major group of thrombolyzed AIS patients who fail to reanalyze (>60%), t-PA might trigger unintended and potentially harmful immunosuppressive consequences instead of beneficial reperfusion. To test this hypothesis, we performed an exploratory study to investigate the immunomodulatory properties of t-PA treatment in a mouse model of ischemic stroke. Methods: C57Bl/6J wild-type mice and plasminogen-deficient (plg-/-) mice were subjected to middle cerebral artery occlusion (MCAo) for 60 minutes followed by mouse t-PA treatment (0.9 mg/kg) at reperfusion. Behavioral testing was performed 23 h after occlusion, followed by determination of blood counts and plasma cytokines at 24 h. Spleens and cervical lymph nodes (cLN) were harvested and characterized by flow cytometry. Results: MCAo resulted in profound attenuation of immune activation, as anticipated. t-PA treatment not only worsened neurological deficit, but further reduced lymphocyte and monocyte counts in blood, enhanced plasma levels of both, IL-10 and TNFα and decreased various conventional DC subsets in the spleen and cLN, consistent with enhanced immunosuppression and systemic inflammation after stroke. Many of these effects were abolished in plg-/- mice, suggesting plasmin as a key mediator of t-PA-induced immunosuppression. Conclusion: t-PA, via plasmin generation, may weaken the immune response post-stroke, potentially enhancing infection risk and impairing neurological recovery. Due to the large number of comparisons performed in this study, additional pre-clinical studies are required to confirm these significant possibilities. Future studies will also need to ascertain the functional implications of t-PA-mediated immunosuppression for thrombolyzed AIS patients, particularly for those with failed recanalization.